2018
DOI: 10.1037/ccp0000309
|View full text |Cite
|
Sign up to set email alerts
|

Towards personalized, brain-based behavioral intervention for transdiagnostic anxiety: Transient neural responses to negative images predict outcomes following a targeted computer-based intervention.

Abstract: Objective Clinical anxiety is prevalent, highly comorbid with other conditions, and associated with significant medical morbidity, disability, and public health burden. Excessive attentional deployment towards threat is a transdiagnostic dimension of anxiety seen at both initial and sustained stages of threat processing. However, group-level observations of these phenomena mask considerable within-group heterogeneity that has been linked to treatment outcomes, suggesting that a transdiagnostic, individual diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 74 publications
1
37
0
Order By: Relevance
“…Specifically, in exploratory analyses we found no evidence that shifts in extradecisional bias over time mediated acute improvements in clinical symptoms (following either ABM or sham training). These analyses were limited by the relatively small sample sizes in the two arms, the (still suboptimal) test-retest reliability of the DDM indices, and by the fact that robust betweengroup differences in clinical outcomes were not observed in the current study (23). Larger or more clinically homogeneous samples may be required to adequately test for such linkages.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Specifically, in exploratory analyses we found no evidence that shifts in extradecisional bias over time mediated acute improvements in clinical symptoms (following either ABM or sham training). These analyses were limited by the relatively small sample sizes in the two arms, the (still suboptimal) test-retest reliability of the DDM indices, and by the fact that robust betweengroup differences in clinical outcomes were not observed in the current study (23). Larger or more clinically homogeneous samples may be required to adequately test for such linkages.…”
Section: Discussionmentioning
confidence: 88%
“…Full methods and primary clinical findings from the randomized controlled trial (clinicaltrials.gov: NCT02303691) have been reported previously (23). In brief, seventy unmedicated patients reporting clinically elevated levels of trait anxiety and associated clinician-rated disability were randomized to receive active ABM (n=49) or a sham control variant (n=21).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was approved by the local Institutional Review Board and informed consent was obtained from all patients. Please note, this sample has also been used in analyses from a prior published study 15 .…”
Section: Methodsmentioning
confidence: 99%
“…Thus, an individual differences approach that examines the timing of threat processing may capture critical, clinically relevant information. For example, prior research has shown that patients who exhibit larger baseline transient neural responses to threatening stimuli across a range of cognitive-affective brain regions display the greatest reductions in clinician-rated vigilance following ABM treatment 15 . This work suggests that patients who display an initial preferential response toward threat in AB-related brain regions are best suited for ABM treatment, which is consistent with prior behavioral work that has shown that initial processing of threat is linked to ABM treatment responses 13,14,16 .…”
Section: Introductionmentioning
confidence: 99%